2023
DOI: 10.3390/v15020264
|View full text |Cite
|
Sign up to set email alerts
|

Unique Variants of Avian Coronaviruses from Indigenous Chickens in Kenya

Abstract: The avian gamma-coronavirus infectious bronchitis virus (AvCoV, IBV; Coronaviridae family) causes upper respiratory disease associated with severe economic losses in the poultry industry worldwide. Here, we report for the first time in Kenya and the Eastern African region two novel AvCoVs, designated IBV/ck/KE/1920/A374/2017 (A374/17) and AvCoV/ck/KE/1922/A376/2017 (A376/17), inadvertently discovered using random nontargeted next-generation sequencing (NGS) of cloacal swabs collected from indigenous chickens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…IBV and rotavirus were therefore the most prevalent in chickens while retroviruses were predominantly detected in ducks. This is consistent with previous studies that were done in other countries that identified these viruses as major pathogens in poultry [37][38][39]. It is noteworthy that most of the chickens sold in Nairobi are transported from Western Kenya, especially Trans Nzoia, and the coastal region, including Kilifi and Kwale counties.…”
Section: Discussionsupporting
confidence: 92%
“…IBV and rotavirus were therefore the most prevalent in chickens while retroviruses were predominantly detected in ducks. This is consistent with previous studies that were done in other countries that identified these viruses as major pathogens in poultry [37][38][39]. It is noteworthy that most of the chickens sold in Nairobi are transported from Western Kenya, especially Trans Nzoia, and the coastal region, including Kilifi and Kwale counties.…”
Section: Discussionsupporting
confidence: 92%
“…Then, samples from 20 birds containing high amounts of NDV RNAs by the rRT-PCT tests (cycle threshold (C T ) cutoff of below 30) were randomly selected for the NGS. Sequencing libraries were prepared from the selected samples using sequence-independent, single-primer amplification [27] and Illumina Nextera TM Flex protocols, followed by paired-end sequencing (600-cycle MiSeq Reagent Kit v3) on an Illumina MiSeq instrument, as previously described [18].…”
Section: Total Rna Extraction and Next-generation Sequencingmentioning
confidence: 99%
“…A recently described Sanger sequencing protocol [18] was used to determine missing bases in ORF1a of the assembled consensus genome sequence (n = 8 nt at position 11,064-11,071) with primers specifically designed for the gap, i.e., IBV-10886F (5 -CTC CTA TGC GGA GTA CGA A-3 ) and IBV-11529R (5 -CAC TGC AGC GTA GAG TCT-3 ).…”
Section: Sanger Sequencingmentioning
confidence: 99%
See 2 more Smart Citations